(untitled) (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to improve students’ ability to write speech texts using the Cooperative Learning Type STAD learning model. This research is a qualitative and quantitative classroom action research (PTK) conducted in two cycles. The research subjects were 27 students of class VIII of SMP Negeri 1 Botomuzoi in the 2025/2026 learning year. The data collection techniques used included observation sheets, essay texts, field notes, and documentation. The results showed a significant increase in students’ abilities. In cycle I, the average student score was 53.52% with the lowest score of 40 and the highest score of 70. Student observation results in cycle I were at an average of 47% in the first meeting and 56% in the second meeting. Meanwhile, in cycle II, the average student score increased to 80% with the lowest score of 65 and the highest score of 90. The results of student observations also increased rapidly to 70% in the first meeting and 82% in the second meeting. Based on these findings, it can be concluded that the Cooperative Learning Type STAD learning model is effective in improving the ability of grade VIII students of SMP Negeri 1 Botomuzoi in writing speech text.